Pengaruh Substitusi Tepung Labu Kuning (Cucurbita Moschata) Terhadap Kadar Β-Karoten Dan Daya Terima Apem - Nurdinayanti, Sisna; Eni Purwani, Eni Purwani S.Si, M.Si; , Pramudya Kurnia, STP, MAgr (2016)
Introduction : The efforts to reduce the imports of rice in Indonesia is by using other food sources such as pumpkin as an alternative way to reduce the use of rice. Pumpkin contain β-carotene in quite high level, 1569 mg/ 100 grams, an alternative food material to reduce the deficiency of vitamin A. To reduce the use of rice flour is by applying food diversification based on local food sources of pro-vitamin A by making food products like apem cake. Objective : The purpose of this study was to determine the effect of pumpkin use as the substituents material of rice flour on β-carotene and receptive level of pumpkin apem. Methods : This study is an experimental research. The design applied in this study is complete randomized design with four different treatments, they were: 0%, 5%, 10%, and 15% with two replications. The level of Β-carotene was obtained by using a spectrophotometer and the receptive level was obtained by using fondness test with 30 panelists. The statistical test was done by using One Way ANOVA , then followed by LSD (Least signifikant Different). Results : Based on the result of ANOVA test, indicated the value of p β-carotene level is 0.000, and the p-value of apem receptive color is 0.000, flavor 0.005, aroma 0.010, texture 0.569 and overall fondness 0.025. Conclusion : There is an effect of pumpkin flour substitution on the level of β-carotene, color, flavor, aroma and overall fondness of pumpkin apem, and there is no effect on the texture of pumpkin apem. The lowest levels of β-carotene is in the apem without pumpkin flour substitution, 0.037 g/ 100 g and the highest is with subtitution at 15%, 0.157 g/ 100 g. The most preferred apem is the one with pumpkin flour substitution 0%. Suggestion : There should be further research of pumpkin apem making to obtain the color, flavor, aroma, and overall fondness of good apem either by reducing the amount of pumpkin flour substitution and adding vanilla to reduce the typical aroma in pumpkin apem. Keywords : Pumpkin Flour, β-Carotene level, Receptive, and Apem Bibliography : 31 (1997 - 2015)